Workshop on Early Crustal Genesis--the World's Oldest Rocks : a Lunar and Planetary Institute workshop, West Greenland, July 21-30, 1985, held at Grønlands Seminarium, Godthåb, Greenland, Denmark - Ashwal, Lewis D.; orcid:0000-0001-7277-9007 (Lunar and Planetary Institute, 1986)
Topics addressed include: a general review of Precambrain crustal evolution; geology and geochemistry of the Archean Craton in Greenland and Labrador; Precambrian crustal evolution in North and South America; and the field excursion to the Ameralik Fjord. sponsored by National Aeronautics and Space Administration . [and others] edited by L.D. Ashwal sponsored by National Aeronautics and Space Administration . [and others] hosted by Greenland Home Rule Government. Fluid-absent metamorphism in the Adirondacks / Valley, J.W. -- Metamorphism and plutonism in the Quetico Belt, Superior Province N.W. Ontario / Percival, J.A. -- Archean sedimentary styles and early crustal evolution / Lowe, D.R. -- A model for the biological precipitation of Precambrian iron-formation / Laberge, G.L. -- Archean metamorphic sequence and surfaces, Kangerlugssuaq Fjord East Greenland / Kays, M.A.